VISTA Is a Novel Broad-Spectrum Negative Checkpoint Regulator for Cancer Immunotherapy - Lines, J. Louise (2014)
In the past few years, the field of cancer immunotherapy has made great progress and is finally starting to change the way cancer is treated. We are now learning that multiple negative checkpoint regulators (NCR) restrict the ability of T-cell responses to effectively attack tumors. Releasing these brakes through antibody blockade, first with anti-CTLA4 and now followed by anti-PD1 and anti-PDL1, has emerged as an exciting strategy for cancer treatment. More recently, a new NCR has surfaced called V-domain immunoglobulin (Ig)-containing suppressor of T-cell activation (VISTA). This NCR is predominantly expressed on hematopoietic cells, and in multiple murine cancer models is found at particularly high levels on myeloid cells that infiltrated the tumors. Preclinical studies with VISTA blockade have shown promising improvement in antitumor T-cell responses, leading to impeded tumor growth and improved survival. Clinical trials support combined anti-PD1 and anti-CTLA4 as safe and effective against late-stage melanoma. In the future, treatment may involve combination therapy to target the multiple cell types and stages at which NCRs, including VISTA, act during adaptive immune responses.